Assessment of oral toxicity and safety profile of cyanidin: acute and subacute studies on anthocyanin - Swathi Suresh; Chitra Vellapandian (Future Science OA, 2024)
Aim: Purified anthocyanins lack a detailed safety profile, prompting the need for comprehensive oral toxicity research. Materials & methods: Sprague-Dawley rats aged 8 weeks received 300 mg/kg cyanidin orally for 14 days in acute toxicity (OECD 423). In the subacute study (OECD 407), adult SD rats were administered 7.5, 15 and 30 mg/kg/day cyanidin orally for 28 days. Results: Acute toxicity indicated an LD50 exceeding 300 mg/kg/day without adverse effects. Subacute toxicity at 7.5–30 mg/kg/day showed well-tolerated responses in both genders. No significant alterations in organ weights, hematological parameters, liver/kidney functions or adverse histopathological findings were observed. Conclusion: Oral cyanidin administration demonstrated high safety and tolerance in rats, establishing a NOAEL at 30 mg/kg/day, affirming cyanidin's safety for oral use.